Antibiotic Residues and Microbial Contamination in Animal-Derived Foodstuffs in Pontianak City, Indonesia - Yuli Arif Tribudi; Oke Anandika Lestari; Musa Alfius; Arif Hidayatullah (Jurnal Ilmu dan Teknologi Hasil Ternak (JITEK), 2020)
Nowadays, demand for foods of animal origin is not limited in terms of quantity, but also the quality, nutritional value and safety for human consumption. Animal-derived foodstuffss can contain biological and chemical hazards through a contamination process. The aim of this study was to detect antibiotic residues and microbial contaminants in animal-derived foodstuffs, i.e. chicken meat, eggs, beef and pork. Samples were collected from different traditional markets (Flamboyan, Mawar, Kemuning and Dahlia) in Pontianak city, Indonesia. Antibiotic residues in foodstuffs were detected using the bioassay method against 4 classes of antibiotics (aminoglycoside, macrolide, penicillin and tetracycline), while the tested microbial contaminants included total plate count (TPC), Escherichia coli, Coliform and Salmonella sp.. Data obtained were analyzed using descriptive statistics. The results showed that antibiotic residues were only detected in chicken products. In chicken meat, 3 (60%) samples tested positive for tetracycline, while in chicken eggs, 3 (60%) and 5 (100%) samples tested positive for aminoglycoside and penicillin, respectively. As per the SNI 7388:2009, of the analyzed samples, 12 (100%) chicken meat, 6 (75%) beef and 5 (100%) pork samples exceeded the limit for TPC; 5 (41.67%) chicken meat and 5 (100%) pork samples exceeded the limit for both coliform bacteria and E. coli; and 7 (58.33%) chicken meat and 3 (37.5%) beef samples were positive for Salmonella. In conclusion, considerable levels of microbial contamination were detected in chicken and beef products in Pontianak city.